498 Assessing Knowledge Silos in the Craniosynostosis Literature. (1st April 2022) - Motiwala, Mustafa; Kumar, Rahul; Amro, Amro; Himel, Sean; Motiwala, Ahmed; Kazmi, Shehroz; Klimo, Paul
Abstract : INTRODUCTION: The surgical treatment of craniosynostosis has traditionally been a multidisciplinary effort, involving pediatric neurosurgeons and plastic surgeons. Advances in treating this condition may result from collaboration between these two specialties, yet there exists a certain risk of sequestering clinical knowledge between the two which may limit continued progress in this regard. METHODS: During September 2020, the Scopus database was queried to identify journal articles related to craniosynostosis. Bibliometric measures were collected for each article, and a database was constructed to assess knowledge sharing between neurosurgeons and plastic surgeons. RESULTS: 5335 articles were identified. 720 (13.5%) were published in a neurosurgery journal with 499 (9.4%) published by neurosurgeons and 665 (12.5%) by neurosurgeons and plastic surgeons collaborating together. As expected, neurosurgeons published primarily (319, 63.9%) in neurosurgical journals, whereas plastic surgeons published most in plastic surgery journals (990, 65.7%). Collaborations were mostly published in plastic surgery journals (326, 49%). After normalizing for years in press, neurosurgeons were observed to be cited significantly less than plastic surgeons (p <0.0001), and articles published in neurosurgery journals were cited at a lower rate than those published in plastic surgery journals. The differential association of terms used in plastic surgery versus neurosurgery article abstracts illustrates the potential sites of knowledge silo formation in the craniosynostosis literature. CONCLUSION: This study demonstrates that a distinct sequestering of knowledge exists between neurosurgeons and plastic surgeons publishing on the topic. Publications by plastic surgeons are more highly cited than by neurosurgeons. While there are certainly specialty-based topics within craniosynostosis, we recommend continued collaboration on all research fronts to avoid sequestration of knowledge and progress.